The scale effect on small-scale modelling of cement block masonry - Sathiparan, N.; Anjalee, W.A.V.; Kandage, K.K.S. (My University, 2016)
This paper discusses the effect of scale on the structural behaviour of cement block masonry under various loading condition. A real scale model test makes possible to obtain data similar to real structures. Financial and practical restrictions on testing real scale models, reduced scale modeling becomes popular to understand the overall behaviour of the structure. But, when the reduced scale model used for testing, the scale might have affected its mechanical properties. Therefore, it is important to understand these changes in order to draw correct conclusion on the prototype behaviour. In general, this study was aimed at understanding of the scale model behaviour of masonry by testing masonry components to determine the masonry properties, looking at a comparison of masonry behaviour at prototype and scale models. The performance of four different scale cement masonry was evaluated. Water absorption, compressive strength of cement block, and compressive, shear and flexural tensile strength of masonry prism were measured on each type of scale model. These mechanical properties are used as indicators of potential performance in masonry. Test results show that; apart from the compressive strength of masonry which not significantly influenced by the scale, all other tested properties, namely; water absorption rate, porosity, shear strength and flexural bond strength seemed to be significantly influenced by the scale.
Keywords: Cement block masonry; Reduced scale